Lost Opportunities to Reduce Periconception HIV Transmission: Safer Conception Counseling By South African Providers Addresses Perinatal but not Sexual HIV Transmission - Matthews, Lynn T.; Milford, Cecilia; Kaida, Angela; Ehrlich, Matthew J.; Ng, Courtney; Greener, Ross; Mosery, F. N.; Harrison, Abigail; Psaros, Christina; Safren, Steven A.; Bajunirwe, Francis; Wilson, Ira B.; et al. (Journal of acquired immune deficiency syndromes, 2014)
Introduction: Safer conception strategies create opportunities for HIV-serodiscordant couples to realize fertility goals and minimize periconception HIV transmission. Patient–provider communication about fertility goals is the first step in safer conception counseling. Methods: We explored provider practices of assessing fertility intentions among HIV-infected men and women, attitudes toward people living with HIV (PLWH) having children, and knowledge and provision of safer conception advice. We conducted in-depth interviews (9 counselors, 15 nurses, 5 doctors) and focus group discussions (6 counselors, 7 professional nurses) in eThekwini District, South Africa. Data were translated, transcribed, and analyzed using content analysis with NVivo10 software. Results: Among 42 participants, median age was 41 (range, 28–60) years, 93% (39) were women, and median years worked in the clinic was 7 (range, 1–27). Some providers assessed women’s, not men’s, plans for having children at antiretroviral therapy initiation, to avoid fetal exposure to efavirenz. When conducted, reproductive counseling included CD4 cell count and HIV viral load assessment, advising mutual HIV status disclosure, and referral to another provider. Barriers to safer conception counseling included provider assumptions of HIV seroconcordance, low knowledge of safer conception strategies, personal feelings toward PLWH having children, and challenges to tailoring safer sex messages. Conclusions: Providers need information about HIV serodiscordance and safer conception strategies to move beyond discussing only perinatal transmission and maternal health for PLWH who choose to conceive. Safer conception counseling may be more feasible if the message is distilled to delaying conception attempts until the infected partner is on antiretroviral therapy. Designated and motivated nurse providers may be required to provide comprehensive safer conception counseling
Keywords: Safer conception; Client–provider communication; HIV prevention; South Africa